City of fortune - Thompson, Victoria (Victoria E.) (Thompson, Victoria (Victoria E.). Counterfeit lady novel, 2022)
Wealthy but uncouth Sebastian Nolan has invited his lawyer, Gideon Bates, and his lovely new wife, Elizabeth, to attend the famous Belmont Stakes. Nolan is anxious for Gideon and Elizabeth to help his daughter, Irene, acquire a bit of polish, now that his venture into thoroughbred racing has allowed them entry into society. He is also hoping to find her a rich potential suitor. Elizabeth is not exactly the society girl Nolan believes her to be, but she is eager to attend the races. Her con artist family has made a lot of money at racetracks, although not from betting on the horses, and she enjoys the excitement of the track. Irene Nolan seems more interested in horses than husbands, and she jumps at the chance to show Elizabeth her horse, Trench, and introduce her to his rider, Cal Regan. Elizabeth soon realizes there is more than just a working relationship between Irene and Cal. But she also knows that Irene's father would never allow his only daughter to marry a jockey. When Cal takes a terrible tumble injuring both himself and Irene's beloved Trench, Elizabeth and Gideon learn that the mishap was not simply bad luck--the horse and rider are victims of sabotage. -- adapted from jacket